Physical activity and risk of gallstone disease: A Mendelian randomization study - Qian, Qilin; Jiang, Han; Cai, Bingyue; Chen, Dingwan; Jiang, Minmin (Frontiers in Genetics, 2022)
Abstract Objective: Given the association between physical activity and the reduced risk of gallstone disease as suggested in observational studies, a Mendelian randomization study was conducted to evaluate the causal nature of this association in genetic epidemiology. Study: Including self-reported and accelerometer-based physical activity traits, the independent genetic variants associated with physical activity were selected from the corresponding genome-wide associations studies as instrumental variables. The summary-level data for gallstone disease were sourced from the UK Biobank (7,682 cases and 455,251 non-cases) and FinnGen consortium (23,089 cases and 231,644 non-cases). Then, two-sample Mendelian randomization analysis was conducted. Inverse variance weight (IVW), weighted median and Mendelian randomization-Egger regression were determined through Mendelian randomization analyses. To ensure the robustness of the results, sensitivity analyses were carried out as well in the study. Results: The negative causality between the genetically predicted accelerometer-based ‘average acceleration’ physical activity and the risk of gallstone disease was suggested in the UK Biobank study (P = 0.023, OR = 0.93, 95% CI: 0.87-0.99), as well as accelerometer-based ‘overall activity’ physical activity and the risk of gallstone disease in the UK Biobank study (P = 0.017, OR = 0.38, 95% CI: 0.17-0.84). with accelerometer-based ‘average acceleration’ physical activity negatively correlated with gallstone disease in the FinnGen consortium data (P = 0.001, OR = 0.94, 95% CI: 0.90-0.97). As for self-reported moderate-to-vigorous physical activity, however, there was no causality observed in both pieces of data. Conclusions: Our studies provide the evidence suggesting a casual association between physical activities and gallstone disease through analysis of genetic data. As indicated by the research results, there is a possibility that a higher level of physical activities could mitigate the risk of gallstone disease.